Spiritual Leadership: Theory and Practices in Schools (a Literature Review) - Hariri, Hasan; Fadhila Bumay, Anitia; Rusdiani, Atik; Sucitra, Diah Ayu (International Journal of Educational Management and Innovation, 2025)
Literature reviews on spiritual leadership lack research, particularly those conducted in the school context between 2020 and 2024. This article explores and reviews the theory and practices of spiritual leadership in schools. The articles used in this literature review were obtained through Google Scholar by entering the keywords "spiritual leadership," "principal leadership," and "school”, with 10 articles selected for further analysis relevant to the key words.  Based on the literature review results, theoretically, in a school context, spiritual leadership can be defined as a model of leadership that intrinsically motivates followers to cultivate vision, hope/faith, and altruistic love that enable followers, including teachers, to enhance their psychological well-being. Practically, (1) teachers' professional well-being is positively impacted by spiritual leadership; (2) principals' performance, students' accomplishments, or academic success are positively impacted by spiritual leadership; (3) organizational citizen behaviors are positively impacted by spiritual leadership. Due to its important impacts, spiritual leadership needs further research to get empirical data in the school context.